Neural Activation in Bilinguals and Monolinguals Using a Word Identification Task - Alejandro E. Brice; Christina Salnaitis; Megan K. MacPherson (Languages, 2023)
The study investigated word recognition during neural activation in monolinguals and bilinguals. We specifically examined word retrieval and blood-oxygenation changes in the prefrontal cortex during a code-mixed word recognition task. Participants completed a gating task incorporating monolingual sentences and Spanish-English code-mixed sentences while using functional near-infrared spectroscopy (fNIRS) to measure blood-oxygenation changes. Word recognition contained four phonotactic conditions: (1) voiceless initial consonants, (2) voiced initial consonants, (3) CV-tense words, and (4) CV-lax words. Bilingual speakers had word-recognition capabilities similar to monolingual speakers even when identifying English words. Word recognition outcomes suggested that prefrontal cortex functioning is similar for early age of acquisition (AOA) bilinguals and monolinguals when identifying words in both code-mixed and monolingual sentences. Monolingual speakers experienced difficulty with English-voiced consonant sounds; while bilingual speakers experienced difficulties with English-lax vowels. Results suggest that localization of speech perception may be similar for both monolingual and bilingual populations, yet levels of activation differed. Our findings suggest that this parity is due to early age of acquisition (AoA) bilinguals finding a balance of language capabilities (i.e., native-like proficiency) and that in some instances the bilingual speakers processed language in the same areas dedicated to first language processing.